Lotion Preparations of Nutmeg Essential oil (Myristica fragrans Houtt) and Repellent Activity Test against Aedes aegypti Mosquitoes - Ikhsanudin, Azis; Raharjo, Satriyo Dwi; Lolita, Lolita (Universitas Ahmad Dahlan, 2025)
Dengue Hemorrhagic Fever (DHF) is a disease caused by the bite of Aedes aegypti mosquitoes infected with the Dengue virus. One natural ingredient that can be used as a repellent to prevent mosquito bites is essential oil. Therefore, this research aims to obtain the right formulation of nutmeg essential oil lotion, determine the influence of adding nutmeg essential oil to the physical properties of the lotion, assess the irritant effect of nutmeg essential oil lotion on the skin, and determine the repellent activity of nutmeg essential oil lotion against female Aedes aegypti mosquitoes. Nutmeg fruit seed essential oil (Myristica fragrans Houtt) was obtained by distillation. The obtained sample was qualitatively tested first using GC-MS to determine its components. Lotion formulation was prepared with varying 1%, 3%, and 6% concentrations. The prepared lotions were tested for their physical properties and repellent activity using female Aedes aegypti mosquitoes as test animals and irritation test. The test result data were statistically analyzed using one-way ANOVA with a confidence level of 95%. The research results obtained standardization of clear nutmeg seed essential oil, yellow in color, with a distinctive nutmeg scent with a refractive index value of (1.475 + 0.001) and a relative compound content of alpha-pinene of 19.40%. Increasing the concentration resulted in decreased adhesive force with a value of (p <0.05), increased spreadability (p <0.05), and increased repellent power (p <0.05). All lotions have a pH of 7, are stable for 6 cycles of storage, and have an irritation index in the very mild to mild irritation category. The conclusion of this research is that nutmeg seed essential oil lotion formulations with various concentration variations, namely formula 1 (1%), formula 2 (3%), and formula 3 (6%), have good physical properties, cause very mild to mild skin irritation, and have the highest repellent activity, which is in formula 3 (6%) at 1098 seconds